Mechanistic insights into Shenqi Dihuang decoction in the treatment of immunoglobulin a nephropathy - Gao, Yachan; Pang, Xinxin; Li, Dongdong; Chen, Xiaoyong; Li, Dongyang; Chen, Zhenyi (Frontiers in Pharmacology, 2026)
BackgroundImmunoglobulin A nephropathy (IgAN) is among the most prevalent glomerular disorders. Shenqi Dihuang decoction (SQD) has demonstrated therapeutic efficacy in various renal conditions, but its effects on IgAN remain insufficiently explored. The present investigation was designed to explore the potential mechanistic actions of SQD in the context of IgAN.MethodsTherapeutic targets of SQD and genes linked to IgAN were sourced from publicly available databases. An intersection analysis was performed to identify drug targets relevant to IgAN, comparing SQD target genes, differentially expressed genes (DEGs) from patients with IgAN versus healthy controls, and module genes associated with the disease. Key candidate genes were identified using feature selection techniques from machine learning, supported by experimental validation of expression patterns. Mechanistic insights were further explored through nomogram construction, gene set enrichment analysis (GSEA), immune cell infiltration profiling, molecular regulatory network reconstruction, and molecular docking simulations. Single-cell RNA sequencing identified key cell populations involved in IgAN pathogenesis, and critical gene expression patterns were assessed within these cells. Additionally, SQD’s protective effects against IgAN were validated using in vitro models.ResultsThe mechanism underlying SQD’s efficacy in IgAN may involve key molecular targets, such as FOS, MCL1, and CCND1 (Cyclin D1 gene). These genes serve as diagnostic markers and are enriched in pathways associated with dicarboxylic acid and amino acid metabolism. Additionally, significant changes in immune cell infiltration were observed. Potential regulatory networks involving 72 miRNAs and 144 transcription factors (TFs), along with high-affinity interactions with active compounds such as cryptotanshinone, tanshinone IIA, and luteolin, were identified. Notably, proximal tubular and intercalated cells play critical roles, with FOS expression upregulated during cellular differentiation. In vitro experiments confirmed SQD’s significant protective effects against injury.ConclusionOur findings proposed three potential key genes—FOS, MCL1, and CCND1—that may contribute to the therapeutic mechanism of SQD in IgAN, providing novel perspectives and candidates for developing targeted therapeutic approaches.